2007
DOI: 10.1209/0295-5075/80/26001
|View full text |Cite
|
Sign up to set email alerts
|

Lehmann effect in compensated cholesteric liquid crystals

Abstract: In 1900, Otto Lehmann observed that the texture of a cholesteric droplet heated from below can rotate continuously (Ann. Phys. (Leipzig), 2 (1900) 649). This observation (which has never been reproduced, to our knowledge) was explained in 1968 by Leslie (Proc. R. Soc. London, Ser. A, 307 (1968) 359) from symmetry arguments accounting for the chirality of the material. In 1982, Éber and Jánossy showed experimentally that a similar thermomechanical effect also exists in a compensated cholesteric (in which the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
26
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 19 publications
8
26
3
Order By: Relevance
“…In previous works [7,8], we showed that q changes linearly with temperature around T c within an excellent approximation. This allowed us to write that (7) where dq dT is a constant.…”
Section: -P2supporting
confidence: 55%
See 2 more Smart Citations
“…In previous works [7,8], we showed that q changes linearly with temperature around T c within an excellent approximation. This allowed us to write that (7) where dq dT is a constant.…”
Section: -P2supporting
confidence: 55%
“…In our experiment, d =25μm and the maximum temperature gradient used was G ≈ 6 × 10 4 • C/m. Knowing that K 2 ≈ 3 × 10 −12 N [7,8] at T c ,w ee s t i m a t et h a t ξ<3 × 10 −12 kg m K −1 s −2 in our CC-8OCB mixture. This conclusion is not incompatible with a previous estimate of a similar coefficient in the liquid crystal 5CB (pentylcyanobiphenyl) in which ξ ∼ 10 −12 kg m K −1 s −2 [17].…”
Section: -P2mentioning
confidence: 80%
See 1 more Smart Citation
“…Although this result was conform to theoretical predictions of Pleiner and Brand [19,20], it seemed to contradict previous experiments ofÉber and Jánossy [21], who found that the "classical" thermomechanical Lehmann coefficient was different from 0 at the compensation temperature. Intrigued by these contradictions, we recently redid the experiment ofÉber and Jánossy and confirmed their results [22,23]. Being thus in disagreement with Pleiner and Brand predictions and with Padmini and Madhusudana findings, we felt it was important to also redo and reanalyze the experiment of Padmini and Madhusudana, while extending it to another geometry.…”
Section: Introductionmentioning
confidence: 65%
“…From these measurements and others described in refs. [22,23], we calculated the dielectric anisotropy ε a = ε − ε ⊥ = 4.8 ± 0.3. We recall that the subscripts and ⊥ refer to the director orientation.…”
Section: Useful Materials Constantsmentioning
confidence: 99%